2022
DOI: 10.21037/jtd-22-258
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of endobronchial valves for the treatment of bronchopleural fistula: a single-arm clinical trial

Abstract: Background: A bronchopleural fistula (BPF) is defined as communication between the bronchus and pleural cavity, and it is a dreaded complication of severe pulmonary disease. Surgical intervention, pleurodesis, and prolonged chest tube drainage have several disadvantages. To overcome these, many attempts have been made to treat BPF with bronchoscopy, especially with the insertion of an endobronchial one-way valve (EBV). Endobronchial valves for the treatment of BPF which had less trauma, relatively short operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Song et al conducted a study on 26 patients, and found that approximately half of them developed BPF after surgery. 8 The effectiveness of EBV treatment was 73.1%, with minimal trauma, a short operation time, and few complications. Another study of 115 BPF cases also showed that EBV treatment was effective in >70% of patients without related complications.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Song et al conducted a study on 26 patients, and found that approximately half of them developed BPF after surgery. 8 The effectiveness of EBV treatment was 73.1%, with minimal trauma, a short operation time, and few complications. Another study of 115 BPF cases also showed that EBV treatment was effective in >70% of patients without related complications.…”
Section: Discussionmentioning
confidence: 91%
“…The patient's preoperative chest tube indwelling time was 7 days, the postoperative drainage tube indwelling time was 34 days, and the time for successful removal of the EBV was 58 days, all of which were shorter than the times reported in Wang et al 7 Mild granulation tissue hyperplasia occurred after EBV removal, but there was no fistula recanalization, which is consistent with previous reports. 7,8 However, further research with a larger patient cohort is necessary to confirm these findings.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The size of BPF > 8 mm is generally unsuitable for bronchoscopic treatment[ 12 , 21 ]. The degree of infection, timing of diagnosis, underlying disease, localization and the size of the fistula may be the critical factors in choosing between surgical and bronchoscopic procedures for treatment[ 8 , 22 , 23 ]. In our case, as the bronchial stump was affected by tuberculosis and the right upper lung was damaged, we did not select the minimally invasive bronchoscopic method as a treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Several novel case reports and case series make note of EBV placement for the management of BPF when surgical intervention cannot be performed. Song et al [58 ▪ ] reported on the use of EBV to close BPF in 26 patients, half of which were postoperative BPF. Overall, 19/26 (73.1%) achieved BPF closure.…”
Section: Management Of Bronchopleural Fistulaementioning
confidence: 99%